2000
DOI: 10.1086/315777
|View full text |Cite
|
Sign up to set email alerts
|

CD8+Cytotoxic T Lymphocyte Responses to Lytic Proteins of Human Herpes Virus 8 in Human Immunodeficiency Virus Type 1–Infected and –Uninfected Individuals

Abstract: T cell immunity to lytic proteins of herpesviruses is important in host control of infection. We have characterized the cytotoxic T lymphocyte (CTL) response to 5 human herpesvirus 8 (HHV-8) homologues of lytic proteins in HHV-8-seropositive individuals. HLA class I-restricted, CD8(+) CTL responses to >/=1 HHV-8 lytic protein were detected in all 14 HHV-8-seropositive study subjects tested, with or without human immunodeficiency virus type 1 (HIV-1) infection, but not in any of 5 HHV-8-seronegative individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 15 publications
(14 reference statements)
2
34
0
Order By: Relevance
“…34 Support for this hypothesis is that there is a CD8 ϩ cytotoxic T-cell response to KSHV that is lower among those infected with HIV-1. [35][36][37] Jung et al 38 found that HAART may enhance efficiency of KS cancer treatment. For example, patients on HAART were able to sustain longer cycles of chemotherapy and ultimately discontinuation of therapy without experiencing relapse.…”
Section: Cd4mentioning
confidence: 99%
“…34 Support for this hypothesis is that there is a CD8 ϩ cytotoxic T-cell response to KSHV that is lower among those infected with HIV-1. [35][36][37] Jung et al 38 found that HAART may enhance efficiency of KS cancer treatment. For example, patients on HAART were able to sustain longer cycles of chemotherapy and ultimately discontinuation of therapy without experiencing relapse.…”
Section: Cd4mentioning
confidence: 99%
“…The peptides derived from kaposin A were a 10-amino-acid-long peptide (amino acids [16][17][18][19][20][21][22][23][24][25] and its shorter version (amino acids [17][18][19][20][21][22][23][24][25]. Since the decamer peptide is reported to have a higher estimated half-time dissociation score and contains both potential epitopes, it was selected for further studies.…”
Section: Identification Of Hla-a2-binding Peptides Derived From Glycomentioning
confidence: 99%
“…[18][19][20][21] At present, very little is known on the immune control of HHV-8 in infected individuals, however, there is evidence indicating the presence of CTL responses specific for latent and lytic antigens. [22][23][24] Since HHV-8-derived epitopes may be regarded as a potential target of specific immunotherapies for the treatment/prevention of HHV-8-associated malignancies, we sought to characterize CTL peptide antigens derived from HHV-8 antigens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased incidence of these diseases in immunocompromised individuals suggests that host immune control may be essential in preventing HHV-8-associated diseases (2). Several studies have demonstrated the anti-HHV-8 specificity of TCR ␣␤ ϩ CD8 ϩ CTL (3)(4)(5)(6)(7)(8)(9)(10). HHV-8 specific CTL responses to latent and lytic viral proteins have been detected during primary HHV-8 infection (11).…”
mentioning
confidence: 99%